Space-time perception and behavioral response of farmers to climate change: Evidence from Sichuan Province, China - Ma, Junqiao; Zhou, Wenfeng; Guo, Shili; Deng, Xin; Song, Jiahao; Xu, Dingde (Frontiers in Ecology and Evolution, 2022)
It is of great significance for global environmental governance to guide farmers to effectively perceive climate change. Based on the survey data of 540 farmers in Sichuan Province, China, this study used binary Logit model and Multinomial Logistic Regression model to explore the effects of farmers' space-time perception of climate change and their interaction effects on farmers' adaptation behavior to climate change. The results showed that: (1) 88.51% of farmers took adaptation measures to climate change, and 61.11% of them took both passive and active adaptation measures. Among the 7 measures, the highest rate of "Increase irrigation" is 23%, and the lowest rate of "Migrant work" is only 5%. (2) The scale difference of farmers' time perception of climate change has a significant positive impact on their adaptive behavior of climate change. In terms of time: climate change perception in the next 5 years > in the next 10 years > in the next 15 years. (3) The scale difference of farmers' space perception of climate change has a significant positive impact on their adaptation behavior to climate change. In other words, spatially, farmers' perception of climate change is global > national > local village (the perception of local province is not significant). (4) Farmers' space-time perception of climate change significantly affects farmers' adaptive behavior. Among them, "farmers' perception of climate change in the next 5 years" and their own "village's perception of climate change" play an important role. This study will help deepen the understanding of farmers' perception of climate change and their adaptive behavior, and provide reference for national policy making.Ad